PERAN FORENSIC ACCOUNTING DALAM PENCEGAHAN FRAUD - Gusnardi ' (Program Studi Pendidikan Ekonomi Universitas Riau, 2012)
Corruption is an issue that is raised, because the perpetrators more daring and moreand more, starting from the lowest in the government (executive), therepresentatives of the people (the legislature) and the self-employed. Everything isrooted. The impact of corruption will cause the number of state money that wasstolen, the impact will be much hindered the provision of development or investmentwill not grow especially foreign investment. The emergence of cases of fraud in thefinancial statements should be found an attempt to prevent or minimize them. Waysof doing this is by studying forensic accounting a professional accountant, studyingForensic Accounting is very important. Because in addition to be reliable inpreparing financial statements, it is also supposedly able to read what is on eitherreport.This paper will discuss how law enforcement can utilize the expertise ofaccountants, especially in the field of forensic accounting to be able to disclose andprovide evidence in support of court decisions relating to corruption. In this paper willalso discuss about forensic accounting and forensic auditing and effort that can bedone to prevent corruption and fraud.